Mammary and splenic neoplasms in a female dog: Case reportt - Machado, Nathália Borstmann; Lehmen, Daniela (Pubvet, 2024)
Regarding mammary and splenic neoplasms in dogs, the surgical therapeutic approach is often the method of choice, given its curative potential and the possibility of subsequent histopathological analysis. In veterinary medicine, the incidence of mammary neoplasms is high, especially in unneutered female dogs. Breast carcinoma in situ, with its histological particularities and clinical behavior, requires a careful diagnosis and precise therapeutic approach, carrying out additional tests such as cytopathology and ultrasound to adequately define the treatment. Surgical excision, associated with the evaluation of adjacent healthy breast tissue, is essential to ensure complete removal of the neoplastic tissue, plus ovariohysterectomy (OVH) is also indicated in addition to a mastectomy. Spleen tumors are similarly common in dogs, especially hemangiosarcoma which is notable for its aggressiveness and high metastatic rate. Therefore, early diagnosis and precise intervention are essential for a good prognosis, with the affected organ being often removed in its entirety. Therefore, we report the case of a female Shih-Tzu dog, 7 years old and weighing 4kg, who presented a nodule in the left M3 upon palpation, measuring <1cm with absence of nodular secretion, change in color, local itching or galactorrhea. The patient was referred for regional mastectomy and OVH after a cytological examination compatible with carcinoma and, in a pre-operative ultrasound examination, a singular hypoechoic nodular formation, discretely heterogeneous, vascularized on Doppler and in close contact with the splenic capsule was noted in the spleen in its medial parietal portion, measuring 0.96 cm in its longest axis. Thus, during intraoperative visual inspection after the OVH and upon approval from the owner, a total splenectomy was opted for and, after histopathological examination, it was confirmed that the organ was affected by hemangiosarcoma. The canine was discharged from the hospital a few hours after surgery, without the subsequent use of adjuvant therapies.